Effect of Tithonia diversifolia extract on the biodegradability of the bioplastics in plantation soil (Pengaruh ekstrak Tithonia diversifolia terhadap biodegradabilitas bioplastik di tanah perkebunan) - . ISROI; Nendyo A WIBOWO; Evi SAVITRI; Deden D ERIS; Agus PURWANTARA (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2018)
Effect of Tithonia diversifoliaextract on biodegradability of the bioplastic was evaluated using plantation soil as natural inoculum. The bioplastic was a composite of cellulose from cacao pod husk, starch and enriched by tithoniaextract. Biodegradation test wasereconducted in the glass jar for 60 days. The carbon dioxide generated from the biodegradation test titrated by 0.1 N sodium hydroxide solutions. The carbon dioxide was measured with 0.1 N HCl and using phenolphthalein followed by methyl orange as indicator. Carbon dioxide was detected in the bioplastic samples but not detected in the conventional plastic sample during the test. Biodegradation of the bioplastic enriched by tithoniaextract was higher than that of the bioplastic without tithoniaextract. Biodegra-dation rate of the bioplastic samples in plantation soil were 0.068 mg CO2/day and 0.178 mg CO2/day for the bioplastic without and with tithoniaextract, respectively. Biodegradation of the bioplastic samples for 45 days were 12.44% and 28.07% for the bioplastic without and with tithoniaextract, respectively. Complete biodegradation of the bioplastic predicted in 244 days and 200 days for the bioplastic without and with tithoniaextract, respectively. [Kata kunci :Tithonia diversifolia, biodegrada-bility, bioplastic, plantation soil]. AbstrakPengaruh ekstrak Tithonia diversifoliaterhadap biodegradabilitas bioplastik dievaluasi dengan menggunakan tanah perkebunan sebagai inokulum alami. Bioplastik yang digunakan adalah komposit selulosa dari kulit buah kakao, pati dan diperkaya dengan ekstrak tithonia. Uji biodegra-dasi dilakukan di dalam botol selama 60 hari. Karbon dioksida yang dihasilkan dari uji biodegradasi diserap oleh larutan natrium hidroksida 0,1 N. Karbon dioksida dititrasi dengan HCl 0,1 N dan menggunakan fenolftalein diikuti dengan metil jingga sebagai indikator. Karbon dioksida terdeteksi pada sampel bioplastik namun tidak terdeteksi pada sampel plastik konvensional.Bioplastik yang diperkaya dengan ekstrak tithonia menghasilkan tingkat biodegradasi yang lebih tinggi dari pada bioplastik tanpa ekstrak tithonia. Tingkat biodegradasi sampel bioplastik di tanah perkebunan adalah 0,068 mg CO2/hari dan0,188 mg CO2/hari masing-masing untuk bioplastik tanpa dan dengan ekstrak tithonia. Biodegradasi sampel bioplastik selama 45 hari adalah 12,44% dan 28,07%berturut-turutuntuk bioplastik tanpa dan dengan ekstrak tithonia. Biodegradasi keseluruhan bioplastik diperkirakan membutuh-kan waktu 244 hari dan 200 harimasing-masinguntuk bioplastik tanpa dan dengan ekstrak tithonia.[Keywords:Tithonia diversifolia, biodegradaibi-litas, bioplastik, tanah perkebunan].